The Impact of Gratitude on Psychological Well-Being of the Al-Hikam Recitation Congregation at Indonesia Islamic Boarding School - Maslahat, Meta Malihatul (Advances in Humanities and Contemporary Studies, 2023)
Humans must feel the problems in their lives during they live in the world. Especially humans who live in a very sophisticated and modern era like today. they more often experience psychological problems because of an imbalance in fulfillment of the biological, psychological, sociological, and spiritual aspects. Therefore, many people feel unwell in these four aspects. From the Islamic perspective, improving welfare in these four aspects, it can be done through an increase in the spiritual aspect. As for the aspect of spirituality in humans which is the determinant for getting psychological well-being, namely faith and gratitude to Allah SWT because with gratitude all enjoyment and welfare in other aspects will increase. In this study, the author will examine how the impact of gratitude on the psychological well-being of the Al-Hikam recitation congregation at the At-Taqy Islamic Boarding School Kalipucang Jepara. This research uses field research with a qualitative approach method. The data collection techniques were obtained through observation, interviews, and documentation. The subjects in this study were 1 caregiver, 2 administrators, and 6 recitation members. In the process of data analysis using data reduction methods, data presentation, verification, and drawing conclusions. The results of this study indicate that gratitude has an impact on the psychological well-being of the Al-Hikam recitation congregation at the At-Taqy Islamic Boarding School Kalipucang Jepara. The indicators of psychological well-being felt by the pilgrims are feeling happier, able to accept God's destiny with grace, feeling calmer, more peaceful, and avoiding various psychological problems.